Criminal minds. The thirteenth season [videorecording (DVD)]. - Mantegna, Joe; Cook, A. J., 1978-; Gubler, Matthew Gray, 1980-; Moore, Shemar, 1970-; Vangsness, Kirsten, 1972-; Brewster, Paget, 1969-; Tyler, Aisha; Rodriguez, Adam, 1975-; Henney, Daniel (Paramount ; ABC Studios / CBS Television Studios, 2018)
Unforeseen threats lead to sudden changes on the team, beginning with the addition of Luke Alvez, whose fugitive tracking skills are put to the test on day one. Emily Prentiss returns from London to take over as the new Unit Chief, joined by Stephen Walker, a seasoned profiler in his own right. This new team must learn to work together to stop the killers, psychopaths, masterminds, hackers, abductors and other dangerous perpetrators that await them in these 22 mind-blowing episodes.